Polyamine-functionalized imidazolyl poly(ionic liquid)s for the efficient conversion of CO2 into cyclic carbonates. Issue 1 (24th November 2021) - Zou, Yizhen; Ge, Yuansheng; Zhang, Qiang; Liu, Wei; Li, Xiaoguang; Cheng, Guoe; Ke, Hanzhong
Abstract : The synergistic effect of polyamine groups and nucleophile (Br − ) significantly improved the catalytic performance of N4 -PIL-2, which can convert epoxides into cyclic carbonates with excellent yields and selectivity under ambient pressure. Abstract : Global warming is becoming a challenging issue due to the emission of a large number of greenhouse gases, mainly CO2 . The transformation of CO2 into chemicals with high additional value is considered a promising and sustainable way to solve the "greenhouse effect". Herein, a series of polyamine-functionalized imidazolyl poly(ionic liquid)s (PILs) modified by triethylenetetramine (TETA) were synthesized as heterogeneous catalysts to convert CO2 into cyclic carbonates. The synergistic effect of nucleophile (bromide anions) and polyamine groups in promoting CO2 conversion was explored by density functional theory (DFT) calculations, which is critical to improve the catalytic performance. When the anions of ionic liquids acted as nucleophiles to attack the epoxide from the C–O bond with less steric hindrance, the substrate epoxide and CO2 can be activated by hydrogen bonding with amine group protons. Therefore, PILs modified by TETA (N4 -PIL- x ) have been verified to possess high efficiency and stable reusability for the cycloaddition of epoxides with CO2 without solvent, metal, and co-catalyst, of which N4 -PIL-2 can achieve 98.0% conversion of epichlorohydrin (ECH) with a turnover frequency (TOF) value as high as 42.4 h −1 under ambient pressure; moreover, the complete conversion of epichlorohydrin is obtained in only 4 h at 1.0 MPa CO2 pressure.